Assessment of the Concentrations of Various Advanced Glycation End-Products in Beverages and Foods That Are Commonly Consumed in Japan - Takeuchi, Masayoshi (PLoS One, 2015)
Dietary consumption has recently been identified as a major environmental source of pro-inflammatory advanced glycation end-products (AGEs) in humans. It is disputed whether dietary AGEs represent a risk to human health. N(ε)-(carboxymethyl)lysine (CML), a representative AGE compound found in food, has been suggested to make a significant contribution to circulating CML levels. However, recent studies have found that the dietary intake of AGEs is not associated with plasma CML concentrations. We have shown that the serum levels of glyceraldehyde-derived AGEs (Glycer-AGEs), but not hemoglobin A1c, glucose-derived AGEs (Glu-AGEs), or CML, could be used as biomarkers for predicting the progression of atherosclerosis and future cardiovascular events. We also detected the production/accumulation of Glycer-AGEs in normal rats administered Glu-AGE-rich beverages. Therefore, we assessed the concentrations of various AGEs in a total of 1,650 beverages and foods that are commonly consumed in Japan. The concentrations of four kinds of AGEs (Glu-AGEs, fructose-derived AGEs (Fru-AGEs), CML, and Glycer-AGEs) were measured with competitive enzyme-linked immunosorbent assays involving immunoaffinity-purified specific antibodies. The results of the latter assays indicated that Glu-AGEs and Fru-AGEs (especially Glu-AGEs), but not CML or Glycer-AGEs, are present at appreciable levels in beverages and foods that are commonly consumed by Japanese. Glu-AGEs, Fru-AGEs, CML, and Glycer-AGEs exhibited concentrations of ≥85%, 2–12%, <3%, and trace amounts in the examined beverages and ≥82%, 5–15%, <3%, and trace amounts in the tested foods, respectively. The results of the present study indicate that some lactic acid bacteria beverages, carbonated drinks, sugar-sweetened fruit drinks, sports drinks, mixed fruit juices, confectionery (snacks), dried fruits, cakes, cereals, and prepared foods contain markedly higher Glu-AGE levels than other classes of beverages and foods. We provide useful data on the concentrations of various AGEs, especially Glu-AGEs, in commonly consumed beverages and foods.